(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Feasibility Analysis of Salak Farming in Macang Village, Bebandem District, Karangasem Regency. This study aims to determine whether salak farming in Macang Village, Bebandem District, Karangasem Regency is feasible. The population in this study were all farmers registered in the Subak Abian Gangga Pawitra Giri Farmer Group. The sampling technique used purposive sampling with a total sample of 15 people. Financial feasibility in terms of four investment criteria, namely Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, Net Benefit and Cost Ratio (Net B/C Ratio), then carried out simultaneously with the data collection process carried out in the field, namely data reduction, data presentation and from the results of data analysis, then conclusions are drawn. The results showed that The results showed that the Net Present Value (NPV) calculation showed a positive value of Rp. 305.294.746 > 0, at an interest rate of 15%, the Internal Rate of Return (IRR) analysis shows an IRR of 19,80% greater than the required rate of return of 15%, Payback Period analysis shows that the payback period the investment capital needed in zalacca farming is the fastest for 3 years and 1 month, and the Probability Index is obtained at 4,754 greater than 1, which indicates that the benefits derived from planting salak are greater than the costs incurred, so that from the fourth analysis From the financial aspect, salak farming in Macang Village, Bebandem District, Karangasem Regency is feasible to develop. To overcome the problems faced by farmers, the Government of Karangasem Regency should routinely conduct agricultural counseling to farming actors so that there is an evaluation of the salak harvest and can add insight to farmers regarding the marketing of salak to make it more profitable for farmers.